Portal vein thrombosis causing neonatal cerebral infarction. Issue 2 (1st September 2002) - Parker, M J; Joubert, G I; Levin, S D
Abstract : Neonatal cerebral infarction often occurs in the absence of known risk factors. Two such cases are described in which portal vein thrombosis was documented during two dimensional echocardiography. In both cases, infarcts were consistent with embolic events. A novel mechanism is proposed, which may explain some cases of "idiopathic" neonatal cerebral infarction.